FLAME‐D Database: An Integrated System for the Study of Archaeometallurgy. (19th October 2020) - Perucchetti, L.; Bray, P.; Felicetti, A.; Sainsbury, V.; Howarth, P.; Saunders, M. K.; Hommel, P.; Pollard, M.
Abstract : This paper discusses the reorganisation of archaeometallurgical legacy data for future research. When archaeometallurgical research aims to answer questions that involve significant movements of raw material or metal objects, it needs to rely on large sets of data. These data are available but scattered across hundreds publications, where they are differently organised, based on the focus of the original papers. The FLAME‐D database aims to collect this corpus of data and include it in a versatile structure that also maintains the information about the original data organization. The production of such a database requires transparent data transformations. The database is complemented by a series of online tools that make data available to answer new questions.